1990
DOI: 10.1002/arch.940130304
|View full text |Cite
|
Sign up to set email alerts
|

In vitro rearing of parasitoids: Role of host factors in nutrition

Abstract: Evidence for the role of host components in the growth and development of parasitoids i s briefly reviewed, and implications concerning the development of in vitro culture media are discussed. In vitro development of the entomophagous parasitoids Eucelataria bryani Sabrosky (Diptera: Tachinidae) and Trichograrnma pretiosum Riley (Hymenoptera: Trichogrammatidae) i s dependent on low-molecular-weight host chemicals. Asparagine, but not aspartic acid, and several other free amino acids are essential dietary ingre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…However, this diet has still limitations in terms of fecundity, with 60 % of the females failing to lay eggs and dying shortly after molting to the adult stage. Nettles (1990) and Grenier and De Clercq (2003) noted that adding insect components such as hemolymph to artificial media enhanced their acceptability and improved their nutritional quality for a number of entomophagous insects. Hemolymph of lepidopteran larvae or pupae has been used in artificial media for parasitoid wasps, especially for Trichogramma species.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, this diet has still limitations in terms of fecundity, with 60 % of the females failing to lay eggs and dying shortly after molting to the adult stage. Nettles (1990) and Grenier and De Clercq (2003) noted that adding insect components such as hemolymph to artificial media enhanced their acceptability and improved their nutritional quality for a number of entomophagous insects. Hemolymph of lepidopteran larvae or pupae has been used in artificial media for parasitoid wasps, especially for Trichogramma species.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have demonstrated that the use of insect materials in artificial media can enhance survival and oviposition of entomophagous insects (Grenier and De Clercq 2003). For instance, many artificial media for egg parasitoids of the genus Trichogramma contain lepidopteran pupal hemolymph and/or pupal holotissues to stimulate egg laying by the parasitoid females or to provide adequate nutrition for development of the larvae (e.g., Liu et al 1979;Strand and Vinson 1985;Nettles 1990;Lü et al 2012). Also, the fecundity of the predatory anthocorid Orius insidiosus (Say) was significantly increased when the bugs were fed on an artificial diet supplemented with a cell line derived from eggs of the Indian meal moth Plodia interpunctella Hübner (Ferkovich and Shapiro 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Insect hemolymph may provide some unknown essential growth factors that play a decisive role in the immature development of a parasitoid. Media developed for insect parasitoids often include host egg derivatives, host hemolymph, and/or pupal holotissues, which are used to stimulate oviposition by parasitoid females, to provide adequate nutrition for the developing larvae, and/or the necessary factors to stimulate parasitoid pupation (Nettles, 1990). Heslin et al (2005a,b) used insect cell lines to improve the larval feeding of Trichogramma pretiosum Riley, yielding 60% larval survival, but less than 20% pupal survival.…”
Section: Discussionmentioning
confidence: 99%
“…These diets would usually include host egg derivatives, host hemolymph and/or pupal holotissues. Such components would either be used to stimulate egg laying by parasitoid females or to provide adequate nutrition and/or the necessary factors to stimulate parasitoid pupation (Nettles 1990). A variety of other components were mixed with such insect-derived molecules to ascertain for a suitable medium for egg laying and larval development, such as egg yolk, milk, yeast/casein hydrolysate, malt solution, bovine fetal serum, salt solutions, and antibiotics, among others (see Grenier 1994 for review).…”
Section: Artificial Diets -Compositionmentioning
confidence: 99%